Narrating Multilingual Realities: A Stylistic And Linguistic Study Of Code-Switching in Chimamanda Ngozi Adichie’s Americanah - Singh, Raj Kishor (Nepalese Linguistics, 2025)
This paper examines code-switching as a stylistic and linguistic device in Chimamanda Ngozi Adichie’s Americanah, exploring how multilingual narration expresses diasporic identity, cultural negotiation, and resistance. The study draws on Gumperz’s distinction between situational and metaphorical code-switching, Myers-Scotton’s Markedness Model, Leech and Short’s stylistics, and postcolonial theories from Bhabha and Ngũgĩ wa Thiong’o to frame its analysis. Adichie’s integration of Standard English, Nigerian Pidgin, Igbo, and African American Vernacular English (AAVE) creates a polyphonic narrative that reflects hybridity and postcolonial fragmentation. Code-switching is shown not as incidental realism but as a deliberate literary strategy that asserts cultural authenticity and challenges linguistic hierarchies. By highlighting how language choices mirror identity shifts and social positioning, the paper argues that code-switching in Americanah functions as both an aesthetic device and a political act. Ultimately, the study bridges sociolinguistics and literary criticism, demonstrating language’s role in shaping postcolonial identity and narrative complexity.